Resistivity characteristics of Conductive Rubber Sheet and Quantum Tunnelling Composite Pills for robotic hand tactile sensing application / Ahsana Aqilah Ahmad - Ahmad, Ahsana Aqilah (2014)
The thesis presents resistivity characteristics of Conductive Rubber Sheet (CRS) and Quantum Tunnelling Composite (QTC) Pills for robotic hand tactile sensing application. These materials are suitable to be used as transducer in tactile sensing applications. Therefore, the thesis highlights the potential of these two materials as a tactile sensing transducer and later describes the best design parameters for them to be applied as a tactile sensor. In the thesis, the tactile sensing mechanism that includes the operating principle and hardware architecture of the sensor are explained. The experimental setup to determine the fundamental properties of Conductive Rubber Sheet (CRS) and Quantum Tunnelling Composite (QTC) Pills is presented.Resistivity behavior is of the major factors in choosing Conductive Rubber Sheet (CRS) and Quantum Tunnelling Composite (QTC) Pills over the other materials. These materials resistivity need to be tested to ascertain its viability as a tactile sensor. The parameters are voltage supply, the separation gap and sensor construction. The results show the Quantum Tunnelling Composite (QTC) Pills is better in term of reproducibility and stability of the resistance values as compared to the Conductive Rubber Sheet (CRS). However in terms of the sensitivity, Conductive Rubber Sheet (CRS) is better in comparison with the Quantum Tunnelling Composite (QTC) Pills whereby it can cover lower loading range when compared to QTC Pills. However, since the reproducibility of Conductive Rubber Sheet (CRS); 5.05Q standard deviation is lower than the Quantum Tunnelling Composite (QTC) Pills; 2.110. standard deviation, it is more preferable to choose the Quantum Tunnelling Composite (QTC) Pills over Conductive Rubber Sheet (CRS). Furthermore with 5V supply voltage and 0.5mm separation gap, the Quantum Tunnelling Composite (QTC) Pills can perform well similar to the 25V supply voltage. Hence, with the superiority attributes shown, Quantum Tunnelling Composite (QTC) Pills are preferred materials for tactile sensor.